The Effects of Moringa oleifera on Blood IL-6 Levels: A Scoping Review - Muhammad Husni Fansury Nasution; Sarah Rahmayani Siregar; Maulana Ikhsan; Rivhan Fauzan; Dwi Martha Nur Aditya; Putri Eka Sari; Anis En Nabiilah; Muhammad Khalid Mirza; Andi Saputra (Jurnal Multidisiplin West Science, 2026)
Interleukin-6 (IL-6) is widely used as an inflammatory biomarker and has also become a therapeutic target in several inflammatory and malignant diseases. Moringa oleifera (MO) has been reported to possess anti-inflammatory activity, yet evidence regarding its effect on blood IL-6 levels remains limited. This scoping review analyzed available evidence on the effect of MO on blood IL-6 levels. The review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR). A PubMed search was conducted using the keywords ((Moringa oleifera) AND (Interleukin-6 OR IL-6)) AND (blood), covering publications from January 2006 to January 2026. Nine studies met the inclusion criteria. All studies used animal experimental models, measured IL-6 in serum using ELISA, and applied randomized placebo-controlled designs. Most studies reported a significant reduction in blood IL-6 levels after MO intervention. The preparations included aqueous extracts, ethanol extracts, polyphenol extracts, n-butanol fractions, seed powder, and beta-sitosterol isolated from n-butanol seed extract. Overall, MO may have prophylactic potential for chronic inflammatory conditions characterized by elevated blood IL-6 levels; however, standardized preparations and human studies are still needed.